Landscapes of the Uprooted: Displacement in Postwar Europe - Seipp, Adam R. (Holocaust and genocide studies, 2018)
In the ruined landscapes of post-1945 Central Europe, the refugee was both an iconic and a ubiquitous figure. The great Polish writer Tadeusz Borowski, an Ausch